Molecular insights and therapeutic targets for blood-brain barrier disruption in ischemic stroke: critical role of matrix metalloproteinases and tissue-type plasminogen activator - Jin, Rong (2010)
Blood-brain barrier (BBB) disruption, mediated through matrix metalloproteinases (MMPs) and other mechanisms, is a critical event during ischemic stroke. Tissue plasminogen activator (tPA) is the only FDA-approved thrombolytic therapy for acute ischemic stroke, but the efficacy and safety of its therapeutic application is limited by narrow treatment time windows and side effects. Thus, there is a pressing need to develop combinational therapy that could offset tPA side effects and improve efficacy in clinical practice. Recent experimental studies indicate that tPA has previously unidentified functions in the brain beyond its well established thrombolytic activity, which might contribute to tPA-related side effects through MMPs (mainly MMP-9) and several signaling pathways involved in LDL receptor-related protein (LRP), activated protein C (APC) and protease-activated receptor 1 (PAR-1), platelet-derived growth factor C (PDGF-C), and N-methyl-D-aspartate (NMDA) receptor. Therapeutic targeting of MMPs and/or tPA-related signaling pathways might offer promising new approaches to combination therapies for ischemic stroke. This review provides an overview of the relationship between structural components and function of the BBB/neurovascular unit with respect to ischemic stroke. We discuss how MMPs and tPA contribute to BBB disruption during ischemic stroke and highlight recent findings of molecular signaling pathways involved in neurotoxicity of tPA therapy.